Jump attack the formula for explosive athletic performance, jumping higher, and training like the pros - Grover, Tim; Wenk, Shari Lesser (Scribner, 2011)
"Since 1989 when Tim Grover began training Michael Jordan, hundreds of elite competitors have turned to Grover to become stronger, faster, and more powerful, both physically and mentally. From Jordan and Charles Barkley and Hakeem Olajuwon, to Kobe Bryant and Dwyane Wade and countless others, Grover's revolutionary methods have made the best even better, year after year. Jump Attack is Grover's legendary training program. Originally self-published as a 142-page paperback in 2000 with over 300k copies sold (and never available in bookstores) Jump Attack is a cult classic. This edition is completely revised, updated and expanded--and it allows common readers to get results only previously available to elite athletes. The new Jump Attack features a 3-phase, 12-week program based on cutting edge exercise science and designed to produce explosive results. As Grover detailed in Relentless, his guide to a champion's mindset, success is mostly a result of hard work and mental toughness. Jump Attack gives readers the missing piece of the puzzle: the physical program, offering a complete plan to achieve top performance and train like the pros."--Provided by publisher.